Effects of atrazine on growth and sex differentiation, in juveniles of the freshwater crayfish Cherax quadricarinatus - Mac Loughlin, Camila (2016)
The effect of the herbicide atrazine was assayed in early juveniles of the redclaw crayfish Cherax quadricarinatus. Four cohorts of juveniles (a total of 280 animals) were exposed for 4 wk to each one of three atrazine concentrations (0.1, 0.5 and 2.5 mg/L) or a control (0 mg/L), from a commercial formulation having 90% of active principle. At the end of the exposure, no significant (p>0.05) differences in either mortality or molting were noted. However, the weight gain and the protein content of abdominal muscle decreased significantly (p<0.05) in the highest atrazine concentration as compared to control, indicating that atrazine acted as a relevant stressor, although at a concentration higher than those reported in the environment. Besides, the proportion of females increased progressively as the atrazine concentration increases, being significantly (p<0.05) higher than that of controls at the highest concentration assayed. Both macroscopic and histological analysis revealed a normal architecture of gonopores and gonads in both control and exposed animals. The obtained results strongly suggest that atrazine could be causing an endocrine disruption on the hormonal system responsible for the sexual differentiation of the studied species, increasing the proportion of female proportion without disturbing the gonad structure.